2018
DOI: 10.1371/journal.pone.0199800
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of a free radical scavenger on oxidative stress after the relief of partial bladder outlet obstruction in a rat model

Abstract: AimsTo investigate the effect of a free radical scavenger (tempol) after relief of partial bladder outlet obstruction (pBOO) on bladder function in a rat model.MethodspBOO was induced in 50 eight-week-old female Sprague-Dawley rats and relieved 3 weeks later. The rats were divided randomly into 5 groups: sham-operated, tempol-treated for 1 week (Treat-1w) or 3 weeks (Treat-3w), and no treatment for 1 week (nonTreat-1w) or 3 weeks (nonTreat-3w). Awaken cystometrograms were obtained 1 or 3 weeks after relief acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We observed that the bladder wall of the DM group was significantly thicker than that of the control group. This is mainly due to bladder detrusor smooth muscle layer hypertrophy [ 48 ]. Furthermore, the bladder wall thickness of the EA group was significantly lower than that of the sham EA group.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the bladder wall of the DM group was significantly thicker than that of the control group. This is mainly due to bladder detrusor smooth muscle layer hypertrophy [ 48 ]. Furthermore, the bladder wall thickness of the EA group was significantly lower than that of the sham EA group.…”
Section: Discussionmentioning
confidence: 99%
“…Tempol, which is a free radical scavenger, was recently found to prevent BOO-induced thickening of collagen fibers and deposition of these fibers in the detrusor muscle layer via suppression of oxidative stress in a rat model [88]. In this model, the thickness and deposition of collagen fibers in the detrusor muscle layer in rats treated with tempol were significantly less than those in rats that were untreated, and the number of non-voiding contractions per voiding cycle decreased with tempol treatment.…”
Section: Treatments Using Antioxidants For Bladder Outlet Obstructionmentioning
confidence: 99%
“…In this model, the thickness and deposition of collagen fibers in the detrusor muscle layer in rats treated with tempol were significantly less than those in rats that were untreated, and the number of non-voiding contractions per voiding cycle decreased with tempol treatment. In addition, levels of the oxidative stress marker MDA in bladder tissues were significantly lower in tempol-treated rats than in untreated ones [88].…”
Section: Treatments Using Antioxidants For Bladder Outlet Obstructionmentioning
confidence: 99%
“…The intercontraction interval (ICI), pressure threshold, baseline pressure, amplitude voiding pressure, and the number of non‐voiding contractions (NVCs) were measured during the final 30 min. NVCs were defined as small‐amplitude bladder contractions without voiding that were greater than 3 cmH 2 O (Choo et al., 2018). During the final bladder contraction, bladder infusion was stopped and the residual urine volume was measured by withdrawing intravesical fluid through the catheter by gravity and compressing the bladder.…”
Section: Methodsmentioning
confidence: 99%